Lectotype designation for Murex nebula Montagu 1803 (Mangeliidae) and its implications for Bela Leach in Gray 1847 - Daniele, Scarponi; Landau, Bernard; Janssen, Ronald; Morgenroth, Holly; Bella, Giano Della (Zootaxa, 2014)
Bela Leach in Gray is a misapplied and broadly defined genus within the family Mangeliidae Fischer, 1883. Examination of material from the Montagu collection at the Royal Albert Memorial Museum & Art Gallery (RAMM) in Exeter (UK) led to the discovery of six specimens of Murex nebula Montagu 1803 (the type species of Bela). This material is considered to belong to the original lot used by Montagu to define his species. We selected the best-preserved specimen as a lectotype. The lectotype and paralectotypes deposited at the RAMM are fully described and illustrated. Furthermore, diagnostic characters for recognizing B. nebula specimens are presented: protoconch shows weak ornamentation; teleoconch is fusiform with slightly convex whorls characterized by broad, suture-to-suture ribs and dense but weak spiral elements; outer lip is thin; anal sinus is shallow, placed on the shoulder ramp. These key features are of basic importance for: i) restricting the usage of the genus Bela and promoting its stability and consistent usage in literature and ii) separating two allied (and sometimes interchanged) genera: Bela and Mangelia Risso 1826.